Qualitative research and pain: Current controversies and future directions - Tutelman, Perri R. (Can J Pain, 2020)
Much of what we know about the meaning and experience of pain has been facilitated through qualitative research. However, qualitative inquiry continues to be underrepresented in the pain literature relative to quantitative approaches. In this Commentary and Introduction to the Special Issue on Qualitative Research and Pain, we present a collection of high-quality, cutting-edge qualitative studies in pain that highlight theoretical and methodological advancements in the field. The articles included in this Special Issue feature a range of designs (e.g., grounded theory, phenomenology, qualitative description), methods of data collection (e.g., interviews, object elicitation, photovoice), and populations (e.g., immigrant women, individuals with heart disease). Throughout this Commentary we also address three common controversies regarding the quality of qualitative research and the stance we took on them for the Issue. These primarily deal with the procedure-related issues of sample size, generalizability, and saturation. We discuss how a more substantive-centered approach to evaluation—that is, an approach that considers the methodological and theoretical significance of the work—is crucial for advancing qualitative research in pain.